Historical criticism of the Bible methodology or ideology - Linnemann, Eta; Yarbrough, Robert W. (Grand Rapids, MI Baker, 1990)
Includes bibliographical refertences and index.
Keywords: Bible -- evidences, authority, etc; Bible -- hermeneutics; Apologetics -- 20th century; Evangelicalism -- doctrines; Word of God (theology).